CURRENT STATE OF APPLICATION OF HYDRAULIC FRACTURING MICROSEISMIC MONITORING METHODS - Krasnikova, О.; Lisny, G.; Vyzhva, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article is devoted to the review of processing and interpretation of microseismic fracturing monitoring. The need to cover the works related to the intensification of production is caused by the underdeveloped practice of such research in Ukraine. The article describes the world experience of microseismic observations and outlines their prospects on the territory of Ukraine. Considerable attention is paid to the processing and interpretation of fracturing microseismic monitoring data. The choice of technologies is associated with the correct consideration of the geological structure of the prospective area or hydrocarbon field, as well as the previous stages of development of oil and gas fields. The ways of using the world experience of microseismic monitoring of hydraulic fracturing in the conditions of oil and gas provinces of Ukraine are determined.
Keywords: hydraulic fracturing; microseismic monitoring; solving the inverse problem